Recognition of A-U and U-A base pairs in RNA duplexes by modified peptide nucleic acids - Yuan, Zhen (2017)
RNA triplex structures play vital roles in regulating various biological processes, and have attracted a Jot of interest in designing TFOs (triplex-fonning oligomers) that could selectively and specifically bind to the nuclei acid duplex. The PNAs (peptide nucleic acids), with the natural nucleic acids ' entire negatively charged phosphate backbone replaced with a neutral N- (2-aminoethyl)glycine-based structure, could bind to nucleic acids better than their natural counterparts. We tested various modified bases derived from thymine to probe how the hydrogen bonding (acidity of the N3 atom) and base stacking may affect the recognition of an A-U pair by PNA-RNA2 triplex formation. Our non-denaturing polyacrylamide gel electrophoresis and thermal melting results suggest that it is promising to incorporate modified thymine residues into PNAs for selective and sequence-specific recognition of RNA duplexes. The stem loop structure present in the tau pre-mRNA splice site is crucial for the splicing process and contains two U-A base pairs. Modified nucleobases E and S are incorporated into PNAs for recognizing U-A pairs present in the wild type, as well as disease-causing mutated stem loop structure of tau pre-mRNA. Fluorescence binding studies were carried out to measure the binding affinity at physiological pH conditions. The E and S incorporated PNAs demonstrate similar binding affinity towards the target RNA hairpin structures.